Humility breeds authenticity: How authentic leader humility shapes follower vulnerability and felt authenticity - OC, Burak (Institutional Knowledge at Singapore Management University, 2019)
Integrating existing work that considers the self through an interpersonal lens with theories pertaining to leader humility and authenticity, we develop a moderated mediation model that theorizes how and under what circumstances leader humility relates to follower felt authenticity. We argue that followers feel less vulnerable when their leaders express humility and further that this relation becomes weaker as the authenticity of leader humility decreases. We also theorize that follower vulnerability is the mechanism explaining the interactive effect of leader humility and its authenticity on follower felt authenticity at work. Our theoretical model was supported across four studies employing both correlational and experimental designs. These results contribute to our understanding of the interpersonal antecedents of authenticity at work as well as the growing body of research on the impact that leader humility has on important employee outcomes.